Experimental Investigation on the Effect of the Second Stage Evaporation on the Transcritical CO2 Ejector Expansion Refrigeration System - Zheng Lixing; Deng Jianqiang; He Yang (Zhileng xuebao)
An ejector expansion refrigeration cycle with two stage evaporation can not only regulate the exit quality of ejector but also improve the coefficient of performance of system. This experimental study presents the effect of the second stage evaporator on the transcritical CO2 ejector expansion refrigeration system with two stage evaporation. The system performances were investigated with the variation of chilled water flow rate of the second stage evaporator, and the effects were compared with that by the regulation of ejector area ratio, which is the mixing section area to nozzle throat area. The experiment results indicate that the pressure of gas cooler and the first evaporator as well as the compressor mass flow rate increase with the rise of the chilled water flow rate of the second stage evaporator. The larger the ejector area ratio, the higher the gas cooler pressure and the lower the first evaporator pressure and compressor mass flow rate. Furthermore, the entrainment ratio decreases with the increase of chilled water flow rate of the second stage evaporator, while the COP and cooling capacity of the system increase. Especially, the COP and cooling capacity increase largely at lower entrainment ratio. This study provides another excellent regulation approach for ejector expansion cycle.